Biosorption of Mercury (II) from Aqueous Solutions onto Fungal Biomass - Víctor M. Martínez-Juárez; Juan F. Cárdenas-González; María Eugenia Torre-Bouscoulet; Ismael Acosta-Rodríguez (Bioinorganic Chemistry and Applications)
The biosorption of mercury (II) on 14 fungal biomasses, Aspergillus flavus I–V, Aspergillus fumigatus I-II, Helminthosporium sp., Cladosporium sp., Mucor rouxii mutant, M. rouxii IM-80, Mucor sp 1 and 2, and Candida albicans, was studied in this work. It was found that the biomasses of the fungus M. rouxii IM-80, M. rouxii mutant, Mucor sp1, and Mucor sp 2 were very efficient removing the metal in solution, using dithizone, reaching the next percentage of removals: 95.3%, 88.7%, 80.4%, and 78.3%, respectively. The highest adsorption was obtained at pH 5.5, at 30°C after 24 hours of incubation, with 1 g/100 mL of fungal biomass.